Collaborative Governance Of Marine Plastic Waste Of Local Administrative Organizations In Thailand Case Study: Phuket City Municipality (Journal of Namibian Studies : History Politics Culture, 2023)
This article aims to study the collaborative role of Phuket City Municipality in marine plastic waste management among public, private and social sector. Selection of key informants was done by a theoretical sampling method through Collaborative Governance theory. The sample group was divided into 3 groups: government, private and social sector. Since it was a case study, key informants were selected by purposive sampling. The tool used was semi-structured interview and analyzed data by content analysis and triangulation validation.              The findings showed that Phuket City Municipality has created cooperation among government, private and social sector according to the legal authority, clear goals system to drive in every dimension as follows: 1.Government sector: Phuket City Municipality collects, transports, and disposes the waste according to its duty. Phuket Provincial Committee was established to be a driver and integrator in the cluster of local administrative organizations ,  local government agencies , international organizations and ministerial level. 2. Private sector creates cooperation with large waste sources to participate in the management of source waste through social networks. 3. Social sector by building cooperation through community leaders and the community of Phuket City Municipality, promoting the processing of recycled products, creating a provincial environmental foundation to reduce bureaucratic constraints, educating on waste management through municipal schools, creation of communication channels to solve problems with the people, and building cooperation with educational institutions to educate and build cooperation with the public. The cooperation of these 3 sectors is in line with the concept of Collaborative Governance